Plasma Concentrations of sTREM-1 as Markers for Systemic Adverse Reactions in Subjects Treated With Weekly Rifapentine and Isoniazid for Latent Tuberculosis Infection - Wang, Tsai-Yu; Feng, Jia-Yih; Shu, Chin-Chung; Lee, Susan Shin-jung; Chen, Chung-Yu; Wei, Yu-Feng; Lin, Chih-Bin; Huang, Wei-Chang; Su, Wei-Juin; Lin, Shu-Min (Frontiers in Microbiology, 2022)
Background: A regimen consisting of once weekly rifapentine plus isoniazid for 3 months (3HP) is effective for treating subjects with latent tuberculosis infection. However, no reliable biomarker exists for predicting systemic adverse reactions (SARs) during 3HP treatment. Methods: This prospective, multi-center study evaluated the plasma concentrations of soluble triggering receptors expressed on myeloid cells (sTREM)-1 and sTREM-2 in subjects on a 3HP regimen and examined the independent association between these biomarkers and SARs. Results: This study enrolled 80 consecutive subjects received 3HP in Taiwan. Among them, fifty-five subjects without SARs and 25 subjects with SARs were used for analysis. Subjects with SARs had higher concentrations of sTREM-1 at baseline (240.1  19.1 vs 176.7  9.4 pg/mL, P = .001) than those without SARs. Areas under the receiver operating characteristic curves (AUROC) revealed that day 1 plasma levels of sTREM-1 (0.708, 95% CI, 0.584-0.833, P = .003) and sTREM-2 (0.343, 95% CI, 0.227–0.459, P = .025) as well as the sTREM-1/sTREM-2 ratio (0.748, 95% CI, 0.638-0.858, P = .001) had modest discriminative power pertaining to the development of SARs. A sTREM-1 level greater than the cut-off value (>187.4 ng/mL) (hazard ratio [HR], 6.15; 95% CI 1.67-22.70, P = .006) and a sTREM-2 level less than the cut-off value (< 237.2 ng/mL) (HR, 4.46; 95% CI 1.41-14.1, P = .011) were independent predictors of SARs after other variables were controlled. Conclusions: Plasma sTREM-1 and sTREM-2 levels may be useful biomarkers for predicting SARs during 3HP treatment.